2005
DOI: 10.1007/s11172-006-0097-2
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol and its fatty acid esters in native DNA preparations: lipid analysis, computer simulation of their interaction with DNA and cholesterol binding to immobilized oligodeoxyribonucleotides

Abstract: Supramolecular DNA complexes were isolated from rat normal cells and murine tumors. The content of DNA bound lipids (cholesterol and its esters) was determined. The content of cholesterol esters is higher than that of free cholesterol; the lipid content in tumor cells is higher than in normal cells. Using the molecular mechanics approach, it is demonstrated for the first time that cholesterol and its esters with stearic, oleic, linoleic, and linolenic acids bind to the DNA minor groove more strongly than with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…For mixed DNA sequences, the behavior is more complex. It has been shown that cholesterol and its esters can form stable complexes with DNA duplexes (72). Furthermore, inter-cholesterol hydrophobic interactions have been demonstrated to increase the melting temperature of nucleic acid duplexes and triplexes by up to 13°C and 30°C, respectively (73).…”
Section: Discussionmentioning
confidence: 99%
“…For mixed DNA sequences, the behavior is more complex. It has been shown that cholesterol and its esters can form stable complexes with DNA duplexes (72). Furthermore, inter-cholesterol hydrophobic interactions have been demonstrated to increase the melting temperature of nucleic acid duplexes and triplexes by up to 13°C and 30°C, respectively (73).…”
Section: Discussionmentioning
confidence: 99%
“…However, plants and microorganisms are endowed with numerous polycyclic aromatic phenolic compounds, glycosides, and alkaloids [15]. Additionally, though not planar in its native configuration, cholesterol and a plethora of metabolic derivatives of this compound, including sex hormones and steroids, can be aromatized to polycyclic derivatives that can covalently interact with DNA [16]. In this regard it is intriguing that Polk mRNA (but not Poli or Poll mRNA) is particularly highly expressed in the adrenal cortex of embryonic and adult mice, the site of steroid biosynthesis [17].…”
Section: Introductionmentioning
confidence: 99%
“…4 Fatty acids were shown to be stronger bound to the DNA minor groove than to the major groove. The energy of interactions between fatty acids and DNA was found to depend on the number of double bonds and the isomerism of fatty acids, as well as on the nucleotide composition of DNA.…”
mentioning
confidence: 99%